The Islamic Education Students’ Motivation in Learning English - Karimah, Syahadah Albaqiyatul (Journal of Islamic Education, 2023)
The development of globalization era requires everyone to be able to communicate in English, including Islamic education students. This study aims to analyze the Islamic Education students' motivation for learning English. The method used is descriptive-qualitative. The subjects were taken by simple random sampling technique and who completed the questionnaires. The data were taken by online interview questionnaire using Google Form application. The students were asked to answer each question provided. The results showed that there were external and internal factors that influenced students' motivation to learn English. External factors include the lecturer's personality, teaching, and learning methods, and the social environment. Meanwhile, the internal factors are interest and goal.